Accounting for loan loss provisions by Singapore banks : opportunistic behavior or conservative accounting policy. - Tan, Hui Ying. (2008)
This study investigates if banks engage in earnings management during this recessionary period, namely 1997-2001. The banking sector in Singapore is analyzed to detect if accruals, namely loan loss provisions are used to manage earnings.Our findings indicate that banks are purely adopting conservative accounting policy rather than engaging in the opportunistic behavior of managing earnings.